E/(c^2) = mc^2/(c^2)
m = E/(c^2)
Answer:
![\boxed{\mathrm{view \ explanation}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cmathrm%7Bview%20%5C%20explanation%7D%7D)
Step-by-step explanation:
The difference of two cubes formula is given as:
![a^3-b^3 =(a-b)(a^2 +ab+b^2)](https://tex.z-dn.net/?f=a%5E3-b%5E3%20%3D%28a-b%29%28a%5E2%20%2Bab%2Bb%5E2%29)
Factor the equation. Remember the value should add to the b value and multiply to the c value.
x^2-x-12= 0
(x-4)(x+3)=0
Use the zero product property to find roots
x-4=0
x=4
x+3=0
x=-3
Final answer: x=-3, x=4
Answer:
(- 2, - 1 )
Step-by-step explanation:
Given the 2 equations
2x - 3y = - 1 → (1)
x + 4y = - 6 → (2)
Rearrange (2) expressing x in terms of y by subtracting 4y from both sides
x = - 6 - 4y → (3)
Substitute x = - 6 - 4y into (1)
2(- 6 - 4y) - 3y = - 1 ← distribute and simplify left side
- 12 - 8y - 3y = - 1
- 12 - 11y = - 1 ( add 12 to both sides )
- 11y = 11 ( divide both sides by - 11 )
y = - 1
Substitute y = - 1 into (3) for corresponding value of x
x = - 6 - 4(- 1) = - 6 + 4 = - 2
Solution is (- 2, - 1 )